Adapted DBT programme for individuals with intellectual disabilities and problems managing emotions: staff awareness training - Ashworth, Sarah; Tully, Ruth; Mooney, Paul (Emerald, 2016)
Purpose The purpose of this paper is to present the development and evaluation of an original training package for staff members on an awareness of an adapted Dialectical behaviour Therapy programme, the ‘I Can Feel Good’ programme (Morrissey & Ingamells, 2014) designed for individuals with intellectual disabilities and problems managing emotions. The quality and effectiveness of the training was assessed and is reported in this paper. Design/methodology/approach The training was delivered for staff working with individuals with intellectual disabilities in a UK Medium Secure Psychiatric Hospital and was attended by nursing staff. The workshop consisted of six modules: ‘Introduction to the programme’, ‘Mindfulness’, ‘Managing feelings’, ‘Coping in crisis’, ‘People skills’ and ‘Application and summary’. Level of self-reported knowledge, confidence and motivation regarding seven aspects of the training was measured by an evaluation questionnaire completed pre and post training. Findings The results of this study showed that following the training there was a significant increase in self-reported knowledge, confidence and motivation regarding the seven aspects of the training. When perceptions of staff behaviours are observed, although in the right direction, this change was found not to be significant. Originality/value This study highlights the potential for staff training to increase awareness of newly adapted therapeutic programmes for individuals with intellectual disabilities. The staff training may increase their ability and willingness to facilitate the running of such programmes and ability to support learning transfer in group members.